Correction through Omniscience: Electronic Monitoring and the Escalation of Crime Control - Molly Carney (Washington University Journal of Law & Policy, 2012)
This Note focuses upon one of the methods of surveillance and sanctioning used on Lindsay Lohan, electronic monitoring. Frustrated by offender misbehavior, policymakers and courts regularly turn to electronic monitoring (EM) to supervise suspected, convicted, and prior offenders. Considering EM in the context of the criminal system‘s "culture of control" demonstrates the danger in continuing to expand the current system with new EM programs and punishments rather than fixing it. The use of EM surveillance forces consideration of a number of significant issues, ranging from costs to the Constitution. Part I of this Note discusses the development and increased use of EM technologies in the expansive U.S. criminal system. In addition, this Part presents the concept of swift and certain corrections. Part II asks whether EM technologies are ameliorating or simply adding to the current criminal system. The new populations, new industry, and new constitutional concerns institutionalized by EM surveillance, weighed against a lack of clear new results, necessitate caution. Finally, Part III proposes that electronic monitoring only be employed as a true alternative solution to the current U.S. criminal system. The swift and certain paradigm may provide a strong guide in shaping more effective programs. Moreover, the need to assess and reassess the short- and long-term implications of EM surveillance upon individuals and the criminal system is clear. Whether offenders like Lohan, and the system as a whole, will benefit from the growing use of EM surveillance still remains far from certain.
Keywords: electronic monitoring; criminal punishment; criminal electronic monitoring